Analysis of total cost of ownership and cost competitiveness of privately-owned electric vehicles in Nepal - Pathak, Anuj; Subedi, Tek Raj (Journal of Innovations in Engineering Education, 2021)
TThe fossil fuel has been the dominant power source of the transportation all over the world in the past centuries. With the development of electric powertrain technology and growing concern over the detrimental effects of fossil fuel like greenhouse gas emission, the transport sector is transforming to electric globally. The Government of Nepal has also announced different policy measures as well as national plans to adapt to this growing trend of electric vehicle (EV) adoption. Since EVs are considered to have higher capital cost compared to the internal combustion engine vehicles (ICEV), the operational cost differs significantly due to the different maintenance cost, electricity prices and separate tax policies. In this study, a model to calculate the total ownership cost of EVs and their ICEV counterparts is developed. The different parameters like purchase price, annual kilometer travel (AKT), annual tax and insurances, fuel and electricity prices, annual maintenance cost etc. are used to estimate the total cost of ownership per km (TCO/km) for the two wheeler EVs and ICEVs (E2W, ICE2W) and four wheeler EVs and ICEVs (E4W, ICE4W) along with different policies imposed by the government for such vehicles in two different scenario (i.e., before and after finance act 2020/2021). The sensitivity analysis of input parameters and the breakeven distance that makes EVs economical than ICEVs is also calculated.